Iron restriction induces the small-colony variant phenotype in Staphylococcus aureus - Islam, Shariful; Callender, Anna C.; Ho, Quynh N.; Wakeman, Catherine A. (Frontiers in Microbiology, 2022)
Pathogens such as Staphylococcus aureus must overcome host-induced selective pressures, including limited iron availability. To cope with the harsh conditions of the host environment, S. aureus can adapt its physiology in multiple ways. One of these adaptations is the fermenting small colony variant (SCV) phenotype, which is known to be inherently tolerant to certain classes of antibiotics and heme toxicity. We hypothesized that SCVs might also behave uniquely in response to iron starvation since one of the major cellular uses of iron is the respiration machinery. In this study, a respiring strain of S. aureus and fermenting SCV strains were treated with different concentrations of the iron chelator, 2,2' dipyridyl (DIP). Our data demonstrate that a major impact of iron starvation in S. aureus is the repression of respiration and the induction of the SCV phenotype. We demonstrate that the SCV phenotype transiently induced by iron starvation mimics the aminoglycoside recalcitrance exhibited by genetic SCVs. Furthermore, prolonged growth in iron starvation promotes increased emergence of stable aminoglycoside resistant SCVs relative to the naturally occurring subpopulation of SCVs within an S. aureus community. These findings may have relevance to physiological and evolutionary processes occurring within bacterial populations infecting iron limited host environments.